INSTITUTIONALIZATION OF PUBLIC ADMINISTRATION IN THE AGRARIAN SECTOR OF THE ECONOMY OF UKRAINE - GAIDUTSKYI, Andrii; HUTOROV, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
It has been shown that military operations in Ukraine have led to a significant rethinking of the state's role in the economy. Therefore, the approach to the efficiency of public administration of sectoral institutions should be based on impartiality and non-absolutization of sectoral and ministerial authenticity. It has been determined that in the system of management of economic sectors, the ministry of agriculture is almost the only one that exists in each country of the world. At the same time, the functional content of the ministries differs from country to country. In some countries, its main goal is to provide the population with food, while in others it is to realize the export potential of the agricultural sector. It has been argued that the Ministry of Agrarian Policy and Food is functionally required for Ukraine to implement a policy of promoting the development of agro-industrial production and rural areas, deepening processing and exports, increasing the added value of products of final technological stages, and increasing budget and foreign exchange revenues. The key task of such a Ministry for the period before joining the EU should be to pursue a flexible policy of adaptation and harmonization of agricultural interests of Ukraine and the EU in order to prevent the slowdown of integration processes and the transformation of Ukraine into a raw material appendage of more developed countries. Based on the experience of organizing agricultural ministries and agencies, the authors have suggested that the Ministry of Agrarian Policy and Food of Ukraine should focus its activities on the following main functions: lobbying for exports and search for new markets; motivation of processing; adaptation to the EU market and the Common Agricultural Policy; pragmatic political lobbying of the Ukrainian agrarian sector in the EU; concierge support for market participants in Ukraine; budget and grant support; support for rural development; management of the sector on the basis of rational use of water resources, adaptation to climate change and urbanization, preservation of land and soil; management of value chains based on the development of vertical integration in the agri-food sector of the economy; promotion of biodiversity; promotion of agricultural science and innovation.
Keywords: agrarian policy; public administration; ministry of agrarian policy; institutionalization; agrarian sector of the economy; bureaucracy; state power